PERBEDAAN TINGKAT KESEGARAN JASMANI SISWA SD NEGERI 13 BENGKALIS DENGAN SD NEGERI 05 BENGKALIS - Mawardi Mawardi; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
ABSTRACT. This study originated from the curiosity author of the level of physical fitness of students of SD Negeri 13 with SD Negeri 05 Bengkalis. The purpose of this study was to get a real of how the physical fitness level of each student at the same school and to see the differences in the level of physical fitness of students of SD Negeri 13 with SD Negeri 05 Bengkalis. This type of research is the type of comparative research, the research design